The Effect of water depth on the growth and survival rate of Panulirus homarus in floating net cages: Implications for sustainable coastal aquaculture and marine conservation - Efrizal; Sriwahyuni Lubis Amelia; Anwar Riski; Rusnam (BIO Web of Conferences)
Panulirus homarus is a valuable fishery commodity, is in high demand both in Indonesia and internationally. Its cultivation often utilizes floating net cages, where environmental factors, such as water depth, are crucial to the lobster's well-being. This study aimed to analyze the effect of different water depths in floating net cages on the survival rate and growth of P. homarus. The research employed an experimental method with a completely randomized design, consisting of three treatments and five replications. The water depth treatments were WD 01 (4 meters), WD 02 (8 meters), and WD 03 (12 meters). Data were analyzed using analysis of variance. After 60 days of cultivation, the results showed that water depth had no significant effect on the survival rate and growth of P. homarus. The 8-meter depth yielded the highest results with 67±38.19 % of survival rate, 50.33±8.08 g of weight growth, 0.50±0.20 cm of carapace length growth, 0.17±0.15 cm of carapace width growth, 5.11±0.074 %-1 day of specific growth rate, and 25.00±0.76 % of molting rate. Although water depth did not significantly affect outcomes, the 8-meter depth appeared to be optimal for P. homarus in this study.